Solve for x and y using these simultaneous equations: 2x + 3y = 21, y = 2x - 1

Substitute y = 2x - 1 into the first equation.

2x + 3(2x -1) = 21

2x + 6x - 3 = 21

8x = 24

x = 3

Therefore y = 2(3) - 1 = 5

Answered by Alexandra L. Maths tutor

2077 Views

See similar Maths 13 Plus tutors

Related Maths 13 Plus answers

All answers ▸

Solve the following equations showing your method clearly. 3(2x + 9) − 7x = 4(x + 3)


Find x when 2x^2 −x−6=0


Ella is 9 years older than Jasmine, Katherine is 4 times the age of Ella and the sum of all their ages is 72. Work out the ratio of Jasmine's age to Ella's age to Katherine's age, in its simplest form.


How is our blood sugar regulated?


We're here to help

contact us iconContact usWhatsapp logoMessage us on Whatsapptelephone icon+44 (0) 203 773 6020
Facebook logoInstagram logoLinkedIn logo
Cookie Preferences